2016
DOI: 10.1051/matecconf/20164703016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Permanent Deformations and Aging Conditions of Batu Pahat Soft Clay-Modified Asphalt Mixture by Using a Dynamic Creep Test

Abstract: Abstract. This study aimed to evaluate the permanent deformation and aging conditions of BatuPahat soft clay-modified asphalt mixture, also called BatuPahat soft clay (BPSC) particles; these particles are used in powder form as an additive to hot-mix asphalt mixture. In this experiment, five percentage compositions of BPSC (0%, 2%, 4%, 6%, and 8%) by weight of bitumen were used. A novel design was established to modify the hot-mix asphalt by using the Superpave method for each additive ratio. Several laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…A study by [75] had investigated the ductility at the low temperature of 5 • C, and results showed significant improvement of the rheological properties in terms of improving the complex shear modulus and phase angle. A similar trend has been found by [77] as using Bending Beam Rheometer BBR test at −12 • C showed that the modified binder was less susceptible to low temperature cracking. Generally, geopolymer modification of asphalt binders resulted in significantly enhanced asphalt binder properties [2,13,14,73,76,83,84].…”
Section: Performance Characteristics Of Gmamsupporting
confidence: 86%
See 2 more Smart Citations
“…A study by [75] had investigated the ductility at the low temperature of 5 • C, and results showed significant improvement of the rheological properties in terms of improving the complex shear modulus and phase angle. A similar trend has been found by [77] as using Bending Beam Rheometer BBR test at −12 • C showed that the modified binder was less susceptible to low temperature cracking. Generally, geopolymer modification of asphalt binders resulted in significantly enhanced asphalt binder properties [2,13,14,73,76,83,84].…”
Section: Performance Characteristics Of Gmamsupporting
confidence: 86%
“…Geopolymer increased the failure temperature, viscosity, elastic modulus, and complex modulus and enhanced the binder's rutting resistance (Figure 11). The incorporation of higher percentages of geopolymer resulted in improved performance where binders modified with up to 8% high-purity quartz silica fume performed better than the unmodified asphalt binder [77]. The modifier constituents influence the viscoelastic properties of the asphalt binder [5].…”
Section: Rheological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various techniques are employed for the characteristics of asphalt cement. Road planners and researchers persistently assess the optimal pavement construction criteria, focusing on economic and safety considerations within highway development (Al Allam et al, 2015). Moreover, road surfaces experience consistent exposure to external pressures, encompassing thermal variations and mechanical stress induced by heavy vehicular tra c (Soltani et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Production of Asphalt usually is a by-product of crude oil refining process in petroleum refineries, and it is a complex heterogeneous mixture of hydrocarbons. During the last a few years, several studies in the field of highway materials have been conducted to evaluate using of materials as an asphalt modifier [1], [2]. While conventional inorganic fillers are usually added in percentages varying between 20% and 40% by weight, a typical quantity in micro components may be between 2% and 5% [3].…”
Section: Introductionmentioning
confidence: 99%